Integrating Local Wisdom into Interactive Multimedia to Foster Digital Literacy in Primary School Students - Hasanah, Ummul; Kristanto, Andi; Hendratno (Papanda Publisher, 2025)
This exploratory qualitative study investigates the potential of interactive multimedia infused with local wisdom to foster digital literacy among Grade 4 students at UPT SD Negeri 192 Gresik, Indonesia. Amidst the growing demand for culturally relevant digital education, the integration of local cultural elements into multimedia aims not only to enhance students’ digital competencies but also to preserve indigenous values in learning. Data were collected through participatory observation, semi-structured interviews, and documentation involving students, classroom teachers, and the principal. The findings reveal that the use of culturally embedded multimedia significantly improved student engagement, contextual understanding, and ethical awareness in digital interaction. The multimedia served not merely as a technological tool but as a medium of value transmission, promoting a sense of identity and cultural pride. The study also highlights positive teacher perceptions regarding pedagogical practicality and cultural relevance. Data were analyzed thematically, showing key patterns of increased digital participation and strengthened local identity. The study concludes that the convergence of local wisdom and digital content can effectively cultivate early digital literacy while reinforcing cultural awareness. It recommends that educational stakeholders consider localized digital content development as a strategic innovation in 21st-century learning. This research contributes to the discourse on culturally responsive digital pedagogy and provides practical insights for integrating sociocultural contexts into elementary education. Further research with broader contexts and mixed methodologies is suggested to validate and expand these findings.